And the woman voted: Electoral political challenges of women 70 years after the female vote in Costa Rica - Quirós Jara, Maribelle (2021)
In a town called La Tigra, in San Carlos, Alajuela province, in 1950 a group of humble women became the first female voters in Costa Rica. Within this framework, this article has the general objective of analyzing the challenges and perspectives of the political participation of Costa Rican females as they commemorate the 70th anniversary of the emission of the first feminine vote in the country. For this, the following methodology was used: consultation of the databases of the Tribunal Supremo de Elecciones (TSE) to find out the status of women voters and their participation in national politics; bibliographic review, interviews with specialists and consultation of different media. The information collected allowed to visualize the history of the female suffrage struggles in Costa Rica, as well as the history of the first voters, to finally analyze the current participation of women as voters and in public election positions, according to data collected from the last electoral processes, to end with the establishment of challenges and perspectives of Costa Rican females in electoral political matters.